Co-regulated learning in computer programming: students co-reflection about learning strategies adopted during an assignment - Pedrosa, Daniela (2019)
Higher education students exhibit difficulties in learning computer programming, particularly transitioning from initial programming to advanced programming, so it’s necessary to develop effective teaching strategies. We developed the SimProgramming approach to help students overcome learning difficulties transitioning from entry-level to advanced computer programming, by developing appropriate learning strategies. The students perform a specific set of tasks in a learning environment that simulates business operations, developing a problem-based learning assignment. One of those tasks is filling biweekly individual self-reflection and co-reflection forms. This approach was implemented at the University of Trás-os-Montes e Alto Douro (Portugal), in a 4th semester course of two bachelor programmes: Informatics Engineering and ICT. The students provided 37 biweekly forms, on which we conducted thematic analysis to identify their strategies for co-regulation of learning during the assignment. Students are adopting different strategies in each phase of the approach. Early phases are devoted to organization, planning, and transformation of information, and later phases focus on applying theoretical knowledge and hands-on programming. We recommend including this type of pedagogical task (biwekly self-reflection and co-reflection forms) in educational practices, in view of their contribution to improving self- and co-regulation learning strategies.